Increased inflammation and oxidative stress caused by accumulated metal particle exposure among metro station staff - Zukun Wang; Junjie Liu; Yijun Song; Mingyao Yao; Shihao Wen; Wenzhe Shang; Mingtong He; Yushuang Wang; Junjie He (PLoS ONE, 2025)
Metro is a significant part of world transport, delivering over 58 billion passengers annually. Train operation processes generated PM rich in heavy metals in the station, but the natural ventilation underground is poor leading to a high PM exposure indoors. Though PM pollution in metro stations was reported widely, there is limited evidence of the adverse health effect of metro station PM. This study collected urinary samples from 74 metro station staff from three different metro stations in Tianjin for 8-OHdG, IL-6, MDA, GSH and T-AOC tests using commercial kits. PM samples were collected for metal composition tests using ICP-MS and oxidative potential test using DTT method. The average PM 2.5 concentration was 31.5 ± 12.4 μg/m 3 , meeting the Standard for indoor air quality in China. However, the indoor concentrations of Zn, Cu, Mn, and Fe were ten times higher than those in the ambient air, inferring a higher exposure level of metal particles. Urinary 8-OHdG, MDA, and IL-6 of senior employees (length of service in the metro station > 5 years) were significantly higher than new employees but not related to age, suggesting a significant influence on individual’s inflammation and oxidative stress led by PM exposure. Identified as characteristic elements in the metro stations, Mo and Ni, were also found significantly correlated with urinary IL-6 and GSH. The findings indicates that chronic metal PM exposure in the metro station may induce oxidative stress and inflammation. However, the accumulated PM 2.5 concentration showed a poor relation with biomarkers except for IL-6. Accumulated oxidative potential of PM was significantly correlated with urinary IL-6, 8-OHdG, GSH, and T-AOC. This result suggested the accumulated oxidative potential of PM as a better evaluation method of health influence led by PM rather than mass concentration.